High-performance epoxy vitrimer from commercial epoxy-anhydride with reprocessable and chemical degradable properties - Gao, Liang; Wang, Hao; Yao, Xuan; Zheng, Zhiran; Wang, Liyu; Wang, Zixuan; Wang, Yonggui; Zhang, Baoyan; Jing, Xianghai; Wu, Jianqiao (Frontiers in Materials, 2025)
Epoxy vitrimer is a kind of recyclable polymer that can reconstruct their network topology through chemical bond exchange reactions, providing an innovative solution for the thermosets recycling dilemma. However, current vitrimers have not yet reached the level of commercial epoxy resins, especially in performance and preparation process. In this study, high-performance epoxy vitrimer has been prepared using a commercial epoxy-anhydride. In the presence of 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as an internal catalyst, both mechanical and thermal properties were improved significantly because of the complete curing reaction facilitated by TBD. With the addition of catalyst TBD, the tensile strength, modulus, elongation at break and the glass transition temperature (Tg) of materials increased from 49.12 to 79.27 MPa, 2080.96 to 2266.19 MPa, 2.78% to 3.86%, and 94°C to 132°C respectively. Meanwhile, the network rearrangement rate improved, in which the stress relaxation time (τ*) of networks declined from 19 min to 10 min at 200°C. Taking advantages of dynamic properties, these vitrimers can be reshaped and chemically degraded. Furthermore, carbon fiber composites are fabricated by using vitrimer as matrix, which can be successfully recycled with chemical degradation process at 160°C within 1 h. This research facilitates the development of recyclable epoxy and composites that exhibits significant potential for commercial applications.